'Celibacy is certainly not for me!': Transgressive Sexualities in Male Children in Moses Isegawa's Abyssinian Chronicles. Issue 2 (2nd October 2017) - Mtenje, Asante Lucy
ABSTRACT: Moses Isegawa's representation of young male sexuality in Abyssinian Chronicles draws our attention to sexuality as a mobile process of relation, a provisional, contextually-informed construct which challenges more naturalised assumptions of sexuality as a monolithic biological given. Even though there may be attempts by various state and ideological apparatuses to police sexualities and bodies, whether via explicit control or the more subtle inculcation of ideas and behaviours, this coercive facet of identity is not easily fixed into conformity. People create spaces – rhetorical, experiential, imaginative – in which to live difference, in the form of resistance, perhaps, or simply as modes of being and imagining that escape the material and discursive governance of normative categories. This paper examines the intertwining concepts of religion and culture and their role in the production of assumed sexual truths. I consider how these are variously realised through institutions such as schools, church and family, and yet how male child characters in Isegawa's novel also embody and transgress the socio-cultural norms that these institutions espouse.